2016
DOI: 10.1186/s12978-016-0135-y
|View full text |Cite
|
Sign up to set email alerts
|

Community perceptions of pre-eclampsia and eclampsia in southern Mozambique

Abstract: BackgroundSub-Saharan Africa has the highest maternal mortality ratio at 500 deaths per 100,000 live births. In Mozambique maternal mortality is estimated at 249-480 per 100,000 live births and eclampsia is the third leading cause of death. The objective of this study was to describe the community understanding of pre-eclampsia and eclampsia, as a crucial step to improve maternal and perinatal health in southern Mozambique.MethodsThis qualitative study was conducted in Maputo and Gaza Provinces of southern Moz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 8 publications
(9 reference statements)
4
42
2
3
Order By: Relevance
“…Sub-Saharan Africa has the highest maternal mortality ratio at 500 per 100,000 live births 5. In Zimbabwe, preeclampsia and eclampsia are the third leading causes of death after AIDS-defining conditions and postpartum hemorrhage 6.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa has the highest maternal mortality ratio at 500 per 100,000 live births 5. In Zimbabwe, preeclampsia and eclampsia are the third leading causes of death after AIDS-defining conditions and postpartum hemorrhage 6.…”
Section: Introductionmentioning
confidence: 99%
“…In Mozambique, such limitations include poor access to diagnostic testing as mentioned above, as well as limited knowledge of preeclampsia and delays in seeking care. [15][16][17][18] In response to the gaps in care discussed above, we determined the ability of maternal plasma-free PlGF to identify those women at risk of complicated preeclampsia when preeclampsia was suspected in the course of antenatal care in Maputo city, Mozambique.…”
Section: Hypertensionmentioning
confidence: 99%
“…This finding was identical to other studies in Africa and Asia. 3,[10][11][12] Only 15% of women knew that preeclampsia was a pathology specific to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In most developing countries, women and the community believe that high blood pressure during pregnancy is due to a stress of everyday life. 3,[10][11][12] In India, Vidler et al, reported that dietary deficiency stress is the main cause cited by patients. 10 In Mozambique, stress and conflict with the in-laws would be the causes according to the patients.…”
Section: Discussionmentioning
confidence: 99%